2021
DOI: 10.3390/e23060709
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Uniform Magnetic Field and Internal Heated Vertical Plate on Ferrofluid Free Convection and Entropy Generation in a Square Chamber

Abstract: The heat transfer enhancement and fluid flow control in engineering systems can be achieved by addition of ferric oxide nanoparticles of small concentration under magnetic impact. To increase the technical system life cycle, the entropy generation minimization technique can be employed. The present research deals with numerical simulation of magnetohydrodynamic thermal convection and entropy production in a ferrofluid chamber under the impact of an internal vertical hot sheet. The formulated governing equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Finally, GFEM was invented to solve the abovementioned fundamental equations (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and suitable boundary conditions (20)(21)(22). The Galerkin weighted residual approach was utilized to transform these fundamental equations into integral equations.…”
Section: Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, GFEM was invented to solve the abovementioned fundamental equations (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and suitable boundary conditions (20)(21)(22). The Galerkin weighted residual approach was utilized to transform these fundamental equations into integral equations.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Their outcomes showed that heat transmission was affected by the magnetic intensity in a nonmonotonic manner. Sivaraj et al [20] digitally assessed the performance of a magnetic intensity on the convective flow of a ferrofluid in a chamber containing a vertical heated sheet. Outcomes showed that the rate of entropy generation witnessed a rise when an isothermal lamina was replaced by a non-uniformly warmed one, while it was reduced when an ideal inclined Lorentz force was set.…”
Section: Introductionmentioning
confidence: 99%
“…Their outcomes showed that heat transmission was affected by the magnetic intensity in a non-monotonic manner. Sivaraj et al 18 digitally assessed the performance of a magnetic intensity on the convective flow of a ferrofluid in a chamber containing a vertical heated sheet. Outcomes showed that the rate of entropy generation witnessed a rise when an isothermal lamina was replaced by a non-uniformly warmed one, while it was reduced when an ideal inclined Lorentz force was set.…”
Section: Introductionmentioning
confidence: 99%